Consequences of chromsome18q deletions. (3rd August 2015) - Cody, Jannine D.; Sebold, Courtney; Heard, Patricia; Carter, Erika; Soileau, Bridgette; Hasi‐Zogaj, Minire; Hill, Annice; Rupert, David; Perry, Brian; O'Donnell, Louise; Gelfond, Jon; Lancaster, Jack; et al.
<x xml:space="preserve">Abstract</x> Providing clinically relevant prognoses and treatment information for people with a chromsome18q deletion is particularly challenging because every unrelated person has a unique region of hemizygosity. The hemizygous region can involve almost any region of 18q including between 1 and 101 genes (30 Mb of DNA). Most individuals have terminal deletions, but in our cohort of over 350 individuals 23% have interstitial deletions. Because of this heterogeneity, we take a gene by gene approach to understanding the clinical consequences. There are 196 genes on 18q. We classified 133 of them as dosage insensitive, 15 (8%) as dosage sensitive leading to haploinsufficiency while another 10 (5%) have effects that are conditionally haploinsufficient and are dependent on another factor, genetic or environmental in order to cause an abnormal phenotype. Thirty‐seven genes (19%) have insufficient information to classify their dosage effect. Phenotypes attributed to single genes include: congenital heart disease, minor bone morphology changes, central nervous system dysmyelination, expressive speech delay, vesicouretreral reflux, polyposis, Pitt‐Hopkins syndrome, intellectual disability, executive function impairment, male infertility, aural atresia, and high frequency sensorineural hearing loss. Additionally, identified critical regions for other phenotypes include: adolescent idiopathic scoliosis and pectus excavatum, Virchow‐Robin perivascular spaces, small corpus callosum, strabismus, atopic disorders, mood disorder, IgA deficiency, nystagmus, congenital heart disease, kidney malformation, vertical talus, CNS dysmyelination growth hormone deficiency and cleft palate. Together these findings make it increasingly feasible to compile an individualized syndrome description based on each person's individuated genotype. Future work will focus on understanding molecular mechanisms leading to treatment. © 2015 Wiley Periodicals, Inc.